Reframing Sexual Education Through Islamic Values: A Digital Innovation for Teachers of Students with Visual Impairments - Novaldi, Irvan Dwi; Chamidah , Atien Nur (Alfuad: Jurnal Sosial Keagamaan, 2026)
Sexual education for students with visual impairments remains underdeveloped within Islamic educational contexts, where moral sensitivity and inclusive pedagogical approaches are both critically needed. Despite increasing awareness of child protection, few studies have integrated Islamic ethical principles into structured digital learning resources for teachers in special education settings. Addressing this gap, this study develops and evaluates an Islamic values-based e-module designed to support teachers in delivering sexual education to students with visual impairments. This research employed a Research and Development (R&D) approach using the ADDIE model (analysis, design, development, implementation, and evaluation). The module was validated by a subject-matter expert and a media expert, and its effectiveness was tested with six teachers from special schools (SLB) in Riau Province, Indonesia. The results indicate that the module achieved a feasible level of material validation (79%) and a highly feasible level of media validation (93%). Teachers’ evaluations showed a high level of usefulness (97%), and statistical analysis using the Wilcoxon Signed Rank Test demonstrated a significant improvement in teachers’ understanding (p = 0.026). Beyond its technical feasibility, the module integrates Islamic moral concepts such as modesty (ḥayā’), self-respect (‘iffah), and bodily responsibility (amānah al-jasad), aligning sexual education with Qur’anic and prophetic guidance. The findings suggest that integrating Islamic pedagogy into digital sexual education resources enhances teachers’ competence while reinforcing ethical and spiritual dimensions of inclusive education. This study contributes theoretically to the discourse on Islamic moral pedagogy and practically to the development of value-based digital innovations in special education contexts.